175k views
5 votes
4r + 6r - 13 = 7r + 5

User Eklavya
by
6.0k points

2 Answers

7 votes

hi there! here's my answer for you...

Answer:

r = 6

Explanation:

4r + 6r - 13 = 7r + 5

10r - 13 = 7r + 5

10r - 13 + 13 = 7r + 5 + 13

10r = 7r + 18

10r - 7r = 7r + 18 - 7r

3r = 18

3r/3 = 18/3

r = 6

hope this helped. have a good one!

User Cpugourou
by
4.8k points
5 votes

Answer:

r = 6

Explanation:

4r + 6r - 13 = 7r + 5

10r - 13 = 7r + 5

10r - 7r = 13 + 5

3r = 18

r = 6

User Widavies
by
5.3k points